Aldosterone, From (Patho)Physiology to Treatment in Cardiovascular and Renal Damage - Waanders, Femke; V. de Vries, Laura; van Goor, Harry; Hillebrands, Jan-Luuk; D. Laverman, Gozewijn; J. L. Bakker, Stephan; Navis, Gerjan (Current Vascular Pharmacology, 2011)
Aldosterone, a steroid hormone with mineralocorticoid activity, is far more than merely a salt-and-water hormone. Aldosterone has a number of non-classical, mineralocorticoid receptor (MR)-mediated actions, including tissue remodeling, modulation of vascular tone and stimulating inflammation and fibrosis, which may fuel progression of end organ damage. Aldosterone breakthrough during blockade of the renin-angiotensin aldosterone system (RAAS) may explain why this treatment regimen only confers partial cardiovascular and renal protection. Of major interest, aldosterone is deleterious only if inappropriately high for its sodium status i.e. high aldosterone and high sodium. The mechanism of sodium dependence of aldosterone-induced renal and cardiovascular damage continues to fascinate. Aldosterone excess increases sodium and fluid retention and consequently increases blood pressure, which, in turn, mediates target organ damage. Moreover, blood pressure independent effects play a role with dissociation of low circulating and high tissue aldosterone levels during high sodium intake and possibly enhanced MR signaling. MR blockade is a valuable strategy, which has potency to halt the progressive end organ damage as observed during current treatments. In heart failure, MR blockade on top of RAAS blockade reduces hard clinical endpoints. Despite encouraging results on the intermediate endpoint proteinuria, long-term data on the efficacy and safety of MR blockade in preventing dialysis and/or cardiovascular endpoints in chronic kidney disease are still lacking. It is obligatory that future clinical studies on the effects of MR blockade on endorgan damage take into account the sodium status.
Keywords: renin-angiotensin aldosterone system